-2(-7n+1)=5n-10

Simple and best practice solution for -2(-7n+1)=5n-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-7n+1)=5n-10 equation:


Simplifying
-2(-7n + 1) = 5n + -10

Reorder the terms:
-2(1 + -7n) = 5n + -10
(1 * -2 + -7n * -2) = 5n + -10
(-2 + 14n) = 5n + -10

Reorder the terms:
-2 + 14n = -10 + 5n

Solving
-2 + 14n = -10 + 5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5n' to each side of the equation.
-2 + 14n + -5n = -10 + 5n + -5n

Combine like terms: 14n + -5n = 9n
-2 + 9n = -10 + 5n + -5n

Combine like terms: 5n + -5n = 0
-2 + 9n = -10 + 0
-2 + 9n = -10

Add '2' to each side of the equation.
-2 + 2 + 9n = -10 + 2

Combine like terms: -2 + 2 = 0
0 + 9n = -10 + 2
9n = -10 + 2

Combine like terms: -10 + 2 = -8
9n = -8

Divide each side by '9'.
n = -0.8888888889

Simplifying
n = -0.8888888889

See similar equations:

| 46+21=11g | | 10-5m=45 | | 3(5y-5)-4= | | 17-11=2(x-7) | | 0.7t-3.2=1.7 | | h=-16t^2+60t+1 | | 7x+19-4x+4= | | -(3x+2)= | | -2-y=9 | | -105=8x | | 15x^2-x-54=0 | | 9j+2-j=8 | | ln(5)=ln(x+2)-ln(2) | | -6/-6 | | 0.5+6.4=4.9-18 | | 5v=9 | | 5x-16=x+6 | | -9x+5=-103 | | 3.2x+2.6=23 | | AX^2=2AX | | 7(x-3)=3x+15 | | 4(2x-3/4)=53 | | 455=O | | -3/4=c+7/10 | | 444/100-1/12=x | | 95=O | | x/2-6=-4 | | 4+m/5=8 | | 13(ab)= | | 2/3y-1=7 | | 9x+12=8x-10 | | 14x^2+4x= |

Equations solver categories